Effect of Coenzyme Q 10 Supplementation on Statin-Induced Myalgia, A Randomized Double-Blind, Placebo-Controlled Study - Rott David; Leibowitz David; Goldenberg Ilan; Klempfner Robert (Journal of Preventive Medicine And Care, 2016)
Objective: Statins are highly effective medications for reducing low-density lipoprotein cholesterol concentrations and cardiovascular events. Their most common side effects are a variety of myopathic complaints, possibly due to reduced circulating Coenzyme Q10 (CoQ10) levels. We sought to determine whether CoQ10 supplementation decreases the rate of myalgia in patients with statin-related myalgia. Methods: Patients treated with a statin for clinical indications who reported statin induced myalgia were eligible. Patients were randomized to treatment with CoQ10 120 mg/day (17 patients) or placebo (20 patients) in a double-blind manner. Treatment was continued for 12 weeks. All patients were instructed to continue taking their prescribed statin as usual. Myalgia score was assessed before intervention and then weekly, for 12 weeks of therapy, using a visual analogue scale (VAS). Results: Over 12 weeks of treatment, myalgia score gradually decreased in both the treatment group and placebo group to the same extent (from 6.2 to 3.3 in the treatment group and from 5.9 to 3.1 in the placebo group), without significant differences between the groups. No significant change was noted between the two groups in the number of patients tolerated statin therapy. Conclusions: CoQ10 does not appear to decrease the rate of myalgia when compared to placebo in patients with statin-related myalgia.
Keywords: Myalgia